The Trespass of the Sign Deconstruction, Theology, and Philosophy - Hart, Kevin (Perspectives in Continental Philosophy, 2022)
The Trespass of the Sign offers a clear and thorough account of the relations between deconstruction and theology. Kevin Hart argues that, contrary to popular thought on the topic, deconstruction does not have an antitheological agenda. Rather, deconstruction seeks to question the metaphysics of any theology. Hart pays particular attention to mystical theology as nonmetaphysical theology